1997
DOI: 10.1080/00288233.1997.9513253
|View full text |Cite
|
Sign up to set email alerts
|

The effects of grazing chicory (Cichorium intybus) and birdsfoot trefoil (Lotus corniculatus) on venison and velvet production by young red and hybrid deer

Abstract: The effects of grazing chicory, Lotus corniculatus, and perennial ryegrass/white clover pasture on growth, voluntary feed intake (VFI), and venison and velvet production was studied in red and hybrid deer from weaning to slaughter at one year of age. Twenty five percent of red and 75% of hybrid stags attained the target slaughter weight (50 kg carcass or greater) when grazing pasture and spiker velvet antler weight was low (approximately 0.2 kg/stag). Mean carcass weight of deer grazing chicory was higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…In contrast to earlier findings in livestock concerning growth-rate depression, Min and Barry [1997] have suggested that grazing on birdsfoot trefoil forage containing condensed tannins actually improved the growth rate of elk (Cervus elaphus). Roe deer (Capreolus capreolus) apparently select forage containing at least some tannin over that lacking tannin [Verheyden-Tixier and Duncan, 2000].…”
Section: Tanninsmentioning
confidence: 67%
“…In contrast to earlier findings in livestock concerning growth-rate depression, Min and Barry [1997] have suggested that grazing on birdsfoot trefoil forage containing condensed tannins actually improved the growth rate of elk (Cervus elaphus). Roe deer (Capreolus capreolus) apparently select forage containing at least some tannin over that lacking tannin [Verheyden-Tixier and Duncan, 2000].…”
Section: Tanninsmentioning
confidence: 67%
“…Such improvements were also observed in other studies when artificially parasitized sheep grazed on chicory containing swards relative to conventional grass/clover mixtures (Marley et al, 2003;Athanasiadou et al, 2007;Kidane, 2010). Min et al (1997) reported increased mean carcass weight of deer grazing chicory compared to deer grazing pasture, due to increased daily live-weight gain. This improvement on chicory compared to other conventional grass/clover mixture is often associated partly to the anti-parasitic effects when animals infected with gastrointestinal parasites are involved (Athanasiadou et al, 2007;Kidane et al, 2009;Kidane, 2010).…”
Section: Lamb Growth and Carcass Yieldmentioning
confidence: 94%
“…The performance of weaned lambs whilst grazing chicory or chicory containing pastures relative to grass/clover mixtures was assessed. We hypothesized that the purported nutritional attributes of chicory relative to grass/clover would be exhibited by improved lamb performance as observed elsewhere with sheep and other livestock (Min et al, 1997;Kidane et al, 2009Kidane et al, , 2010Houdijk et al, 2011) through BW change and higher carcass yield.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Grazing chicory var. Grassland Puna, as compared to ryegrass and Wana cocksfoot has been shown to increase growth in lambs (Komolong et al, 1992;Scales et al, 1995;Fraser and Rowarth, 1996;Barry, 1998;Michalk et al, 2003) and deer (Kusmartono et al, 1996;Min et al, 1997).…”
Section: Introductionmentioning
confidence: 96%